Evidences of ultraviolet visible spectra of hydrogen sulfide scavenging trans-crotonaldehyde induced by hydrogen peroxide through mitochondria of rat heart. Issue 10 (26th November 2017) - Su, Yanbin; Su, Yanwen; Mu, Tongxing; Jiang, Ning; Zhang, Qingsong; Li, Mengjie; Li, Yuan; Li, Shuxin
ABSTRACT: Evidences of ultraviolet visible spectra of hydrogen sulfide scavenging trans-crotonaldehyde (TCA) induced by hydrogen peroxide through mitochondria were probed for the first time. TCA was induced by hydrogen peroxide through mitochondria. When sodium hydrosulfide as hydrogen sulfide donor, comparison with control, ultraviolet visible spectra of TCA decrease were clear. Hydrogen sulfide released by garlic was detected by ultraviolet visible spectroscopy. When garlic as hydrogen sulfide donors, the ultraviolet visible spectra of TCA decrease were very obvious. The findings are strongly recommended that garlic as safe, stable, and controllable hydrogen sulfide donor become a promising drug which is worthy of further study.